Bridging the Gap: The Impact of Gender Equality on CO2 Emissions Across Countries - Diana Sanchez-Olmedo; Paula Ortiz-Yepez; Marco Faytong-Haro (World)
Climate change is one of the greatest challenges to humanity, with carbon dioxide (CO2) emissions being the primary driver. This study examined the relationship between gender equality, measured using the Global Gender Gap Index (GGGI), and CO2 emissions per capita across 49 countries over a 14-year period (2006–2020). Using a fixed-effects regression model, we controlled for structural, economic, and policy variables including population density, GDP per capita, urbanization rate, energy use, the stability of democratic institutions, and environmental policy stringency. Multiple imputations were applied to address missing data, and robustness checks were performed to confirm the validity of the findings. The results indicated that the GGGI is significantly negatively associated with CO2 emissions per capita (β = −0.1403, p < 0.001), suggesting that a 1% improvement in the GGGI corresponds to a reduction of 0.14 metric tons in CO2 emissions per capita. Population density and energy use were also significant predictors, whereas GDP per capita, urbanization rate, and environmental policy stringency showed weaker or non-significant associations. These findings underscore the potential of gender equality to enhance environmental sustainability by improving decision-making processes and policy implementation.